2015
DOI: 10.1371/journal.pone.0144763
|View full text |Cite
|
Sign up to set email alerts
|

The SOS Response Master Regulator LexA Is Associated with Sporulation, Motility and Biofilm Formation in Clostridium difficile

Abstract: The LexA regulated SOS network is a bacterial response to DNA damage of metabolic or environmental origin. In Clostridium difficile, a nosocomial pathogen causing a range of intestinal diseases, the in-silico deduced LexA network included the core SOS genes involved in the DNA repair and genes involved in various other biological functions that vary among different ribotypes. Here we describe the construction and characterization of a lexA ClosTron mutant in C. difficile R20291 strain. The mutation of lexA cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…For instance, a mutation in the lexA gene led to reduced flagellar motility and increased biofilm formation in Pseudomonas aeruginosa [66], as well as in C . difficile [31]. For this reason, the lexA gene seems an interesting target to further study the regulation of biofilm formation in C .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a mutation in the lexA gene led to reduced flagellar motility and increased biofilm formation in Pseudomonas aeruginosa [66], as well as in C . difficile [31]. For this reason, the lexA gene seems an interesting target to further study the regulation of biofilm formation in C .…”
Section: Discussionmentioning
confidence: 99%
“…3234 However, upon severe DNA damage, bacteria may have to make a “fight or flight” decision; either enforce the biofilm for protection or degrade the biofilm in order to escape. This decision may vary depending on the species and situation.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also showed that LexA controls the expression of toxin genes, metronidazole resistance, biofilm production, and sporulation (193). The relationship between sporulation and the SOS system was also found in Bacillus subtilis, through the sda gene (193). Although this gene is absent in C. difficile (194), Walter and colleagues studied how LexA interacted in vitro with the promoter region of another gene associated with sporulation, sspB (194).…”
Section: Sos Responsementioning
confidence: 99%
“…Finally, the features of the SOS response have been studied in C. difficile, and the authors reached the conclusion that the SOS system is related to C. difficile sporulation and that the induction of the SOS system can stimulate biofilm production in this pathogen (193). The same authors also showed that LexA controls the expression of toxin genes, metronidazole resistance, biofilm production, and sporulation (193). The relationship between sporulation and the SOS system was also found in Bacillus subtilis, through the sda gene (193).…”
Section: Sos Responsementioning
confidence: 99%